EFFECT OF SEED DISINFECTION ON BAKANAE DISEASE IN GINKGO BILOBA OUTER SEED COAT EXTRACT - Oh, Tae Seok; park, you jin; Kim, Chang Ho; cho, Young koo; jang, myoung jun (Emirates Journal of Food and Agriculture, 2017)
In research on the control of Bakanae disease using the ginkgo biloba outer seed coat, which currently is being discarded, it was found that ginkgo biloba outer seed coat extract can inhibit the growth of Fusarium fujikuroi at 60% or more at a concentration level of 400mg‧L-1 or more. Disaster-prevention experiments with Ilpumbyeo in which F. fujikuroi was inoculated with the ginkgo biloba outer seed coat extract as a water-dispersible powder were conducted. It was found that to prevent Bakanae disease for 36-48 hours with a treatment solution in which a ginkgo biloba outer seed coat control composition of 7.5% or more was mixed, a control effect of 80% can be used.